Time and Cost Management Analysis Using the Schedule Performance Index (SPI) and Cost Performance Index (CPI) Methods in the Community Health Center Construction Project in Kakaskasen Village, Tomohon City - Grace Yoyce Malingkas (Journal of Social Research, 2025)
Project management is crucial to the success of infrastructure development, including healthcare facility projects such as community health centers. This study aims to analyze time and cost management in a community health center construction project in Kakaskasen Village, Tomohon City. The research method used earned value management (EVM) analysis to evaluate project performance, specifically schedule and cost. The results showed that the project experienced significant time and cost deviations in several construction projects. The schedule performance index was below 1, indicating project delays, while the cost performance index was also below 1, indicating cost overruns. Factors contributing to the delays included poor coordination with relevant parties, delays in material procurement, and unfavorable weather conditions. Proposed recommendations include improving initial planning, strengthening risk management, and more intensive progress monitoring to ensure project completion meets established targets. This research is expected to contribute to improving the management of similar projects.